2020
DOI: 10.3390/su12135384
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Soil Organic Carbon Density Changes from 1980 to 2016 in Shandong Province Dry Farmlands Using the CENTURY Model

Abstract: The changes in cultivated soil organic carbon (SOC) have significant effects on soil fertility and atmospheric carbon dioxide (CO2) concentration. Shandong Province is an important agricultural and grain production area in China. Dry farmland accounts for 74.15% of the province’s area, so studies on dynamic SOC changes would be helpful to understand its contribution to the Chinese national carbon (C) inventory. Using the spatial overlay analysis of the soil layer (1:10,000,000) and the land use layer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…On this premise, the model is run for thousands of years, and the events occurring in the simulation process are arranged through the "EVENT.100" le. Then, by adjusting the parameters of each stage, the simulated value at the end of initialization was close to our measured value (Tang et al, 2020). We obtained the localized CENTURY model so as to suitable for Gannan Alpine meadow.…”
Section: Century Modelmentioning
confidence: 56%
“…On this premise, the model is run for thousands of years, and the events occurring in the simulation process are arranged through the "EVENT.100" le. Then, by adjusting the parameters of each stage, the simulated value at the end of initialization was close to our measured value (Tang et al, 2020). We obtained the localized CENTURY model so as to suitable for Gannan Alpine meadow.…”
Section: Century Modelmentioning
confidence: 56%
“…Some studies using the CENTURY model can accurately simulate the SOC content and its dynamics and applicability in different regions under different changing conditions [35,36]. A number of studies have fully demonstrated the feasibility of the CENTURY model in China and the accuracy of SOC prediction [37,38]. According to others, the CENTURY model is reliable for predicting the impacts of climate change on terrestrial ecosystems [39].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Althoff et al, 2018 [21], estimated an SOCS of 21.0 Mg ha −1 , which was strikingly similar to the average field values observed (20.2 Mg ha −1 ). In addition, for the Shandong province of China, Tang et al [22] estimated the SOC dynamics using the Century model with a coefficient of determination (R 2 ) of 0.722 and a mean error (ME) of 0.37 at p < 0.01. This gives evidence that the Century model promises an effective way of estimating SOC dynamics under a variety of conditions.…”
Section: Introductionmentioning
confidence: 99%